Polish Take on Realism: Poland’s Policy Towards the Former Soviet Countries, 1991–2021 - A. Szeptycki (Международная аналитика, 2021)
This article analyzes Poland’s policy towards the former Soviet space (Poland’s Eastern policy) through the assumptions of the realist theory of international relations. The ﬁ rst part of the article examines the realist theory in international relations (IR). The second – deals with the existing literature on Poland’s foreign policy. The third part analyses the determinants and the goals of Poland’s policy towards the post-Soviet states (history of its relations with the region, ideological determinants, security concerns, etc.). The last part inquires about the evolution of Poland’s policy till current times. The Russian Federation is perceived as a signiﬁ cant threat by Poland. In that context, since the early 1990s, Poland has been seeking solutions to strengthen its security. It aimed to join the North Atlantic Alliance and establish a close partnership with the United States (bandwagoning). This strategy brought substantial eﬀ ects – in 1999, Poland joined NATO, and since it has hosted allied troops. Poland also wanted to develop cooperation with Ukraine (to a lesser degree also with its other post-Soviet neighbors) and bring them closer to the Euro-Atlantic structures. This policy was, in particular, at weakening Russia’s inﬂ uence in the region (balancing). The results of this strategy have been somewhat ambiguous, though. Ukraine has rejected Russia’s sponsored reintegration projects in the post-Soviet space. The process of reforms in that country, however, is slow and uncertain. As for other post-Soviet states, Poland has largely proven unable to inﬂ uence the desired changes.